Antifa : the anti-fascist handbook - Bray, Mark (Historian) (Melville House Publishing, 2022)
In the wake of tragic events in Charlottesville, VA, and Donald Trump's initial refusal to denounce the white nationalists behind it all, the "antifa" opposition movement is suddenly appearing everywhere. But what is it, precisely? And where did it come from? As long as there has been fascism, there has been anti-fascism -- also known as "antifa." Born out of resistance to Mussolini and Hitler in Europe during the 1920s and '30s, the antifa movement has suddenly burst into the headlines amidst opposition to the Trump administration and the alt-right. They could be seen in news reports, often clad all in black with balaclavas covering their faces, fighting police at the presidential inauguration, and on California college campuses protesting right-wing speakers, and most recently, on the streets of Charlottesville, VA. Simply, antifa aims to deny fascists the opportunity to promote their oppressive politics--by any means necessary. Critics say shutting down political adversaries is anti-democratic; antifa adherents argue that the horrors of fascism must never be allowed the slightest chance to triumph again. In this investigation, historian and former Occupy Wall Street organizer Mark Bray provides a one-of-a-kind look inside the movement, including a detailed survey of its history from its origins to the present day -- the first transnational history of postwar anti-fascism in English. Based on interviews with anti-fascists from around the world, Antifa details the tactics of the movement and the philosophy behind it, offering insight into the growing but little understood resistance fighting back against the alt-right.